Copper and zinc concentrations in the breast milk of mothers undergoing treatment for Wilson's disease: a prospective study - Yasuhiro Sato; Hiroko Kodama; Yasumi Anan; Yoichi Izumi; Yasumitsu Ogra (BMJ Publishing Group, 2021)
Objective To evaluate the concentrations of copper and zinc in the breast milk of mothers undergoing treatment for Wilson's disease (WD) and clarify whether they can safely breast feed their infants.Design This was an observational and prospective study in an individual-based case series.Setting Breast milk samples were collected from participants across Japan from 2007 to 2018 at the Department of Pediatrics, Teikyo University in Tokyo. This was a primary-care level study. Clinical data were collected from the participants' physicians.Patients Eighteen Japanese mothers with WD who were treated with trientine, penicillamine or zinc, and 25 healthy mothers as controls, were enrolled.Main outcome measures Whey exacted from the milk was used to evaluate the distribution of copper by high-performance liquid chromatography-inductively coupled plasma mass spectrometry. Copper and zinc concentrations in the breast milk samples were analysed by atomic absorption spectrometry.Results Copper distribution was normal in the breast milk of mothers with WD treated with trientine, penicillamine or zinc. No peak was detected for trientine-bound or penicillamine-bound copper. The mean copper concentrations in the mature breast milk of patients treated with trientine, penicillamine and zinc were 29.6, 26 and 38 µg/dL, respectively, and were within the normal range compared with the value in healthy controls (33 µg/dL). Likewise, mean zinc concentrations were normal in the mature breast milk of patients treated with trientine and penicillamine (153 and 134 µg/dL, respectively vs 160 µg/dL in healthy controls). Zinc concentrations in the breast milk of mothers treated with zinc were significantly higher than those in control milk. All infants were born normally, breast fed by mothers undergoing treatment and exhibited normal development.Conclusions Our results suggest that mothers with WD can safely breast feed their infants, even if they are receiving treatment for WD.